Microforming of titanium - forming behaviour at elevated temperature - Eichenhüller, Bernd; Engel, Ulf (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2008)
Titanium is applied in a wide range of technical applications, especially when high strength in combination with light weight or corrosion resistance is demanded. Titanium is also a popular material for implants in the field of medical technology due to its specific properties like the superb biocompatibility, the elastic behaviour matching that of the human bone, the radiological transparency, and the galvanic neutrality. For the production of microparts, e.g. small-sized implants, manufacturing methods with high accuracy and close tolerances are necessary. If forming processes are used to manufacture the miniaturized medical components, then the size effects occurring with miniaturization have to be considered. The size effects are, among others, responsible for an increased scatter of characteristic process outcomes and a reduced accuracy, thereby reducing the process stability. The limited formability of titanium and titanium alloys at room temperature is also a drawback of forming microparts made of titanium. The main objective of the present study is to investigate the forming behaviour of titanium at microscale and improve its formability by means of forming at elevated temperature.
LFT Import::2019-07-29 (323)
Keywords: Elevated temperature; Microforming; Titanium